Clinical Evaluation of the Effect of Blueberries Consumption on Chronic Diseases, Illness Prevention and Health Promotion - Pavlidou, Eleni; Giaginis, Constantinos; Fasoulas, Aristeidis; Petridis, Dimitris (Natural Products Journal, The, 2018)
Background: The ever-growing concern about achieving quality of life and longevity leads scientists to the search of natural wellness resources. Also, prevention of diseases through food is considered as the driving force of the organism. The beneficial effects of superfoods, such as blueberries, on human health are expected to be proved, putting these effects under the microscope. Objective: Evaluating the effect of blueberries consumption in humans, in order to draw relevant conclusions for their beneficial effect and thus develop food policies and launch target in future searches. Methods: Comprehensive review of published studies of the last decade, using keyword combinations which are derived from the available database. Results: Based on the cited studies, that blueberries consumption reduces degenerative damage caused by free radicals, increases the natural killer cells and inflammatory cytokines, and provides evidence for cellular antioxidant defense against DNA damage, playing also an important role in the anti-cancer nutritional preventive treatment. Moreover, the blueberries consumption protects the elderly from neurodegenerative diseases, which are associated with oxidative stress and aging, improves gait performance, vascular function and insulin sensitivity. It also benefits school-age children's cognitive function. The blueberries consumption also positively influences certain bifidobacterial populations, affects the recovery of visual acuity and operates as a complementary therapeutic factor to reduce the severity of juvenile idiopathic arthritis. Conclusion: The consumption of blueberries is a supplementary function to prevent and cure chronic inflammatory diseases, providing an admirable medical therapy support in order to reduce degenerative damage. However, further studies conducted on larger populations are strongly recommended.
Keywords: Blueberries